2010
DOI: 10.1111/j.1750-3639.2009.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Aβ in Alzheimer's Disease: Relationship to Plaque and Tangle Pathology, APOE Genotype and Cerebral Amyloid Angiopathy

Abstract: Despite accumulating evidence of a central role for oligomeric amyloid beta (Abeta) in the pathogenesis of Alzheimer's Disease (AD), there is scant information on the relationship between the levels and distribution of oligomeric Abeta and those of other neurodegenerative abnormalities in AD. In the present study, we have found oligomeric Abeta to be associated with both diffuse and neuritic plaques (mostly co-localized with Abeta(1-42)) and with cerebrovascular deposits of Abeta in paraffin sections of formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
1
41
2
Order By: Relevance
“…The activities in our A␤O preparations and in AD brain lysates reported here can be attributed to the prefibrillar oligomer according to the Glabe classification, because they were immunoneutralized by the conformation-specific antiserum A11 (8). In AD brains, prefibrillar oligomers and other forms of oligomers were found to accumulate focally as clusters of immunoreactive deposits (67)(68)(69). It is highly likely that focally A␤O can reach the low nanomolar concentrations required for activating microglia in the course of AD development when A␤O progressively accumulates (3).…”
Section: Discussionmentioning
confidence: 87%
“…The activities in our A␤O preparations and in AD brain lysates reported here can be attributed to the prefibrillar oligomer according to the Glabe classification, because they were immunoneutralized by the conformation-specific antiserum A11 (8). In AD brains, prefibrillar oligomers and other forms of oligomers were found to accumulate focally as clusters of immunoreactive deposits (67)(68)(69). It is highly likely that focally A␤O can reach the low nanomolar concentrations required for activating microglia in the course of AD development when A␤O progressively accumulates (3).…”
Section: Discussionmentioning
confidence: 87%
“…The use of an in vivo method, the dynamic PiB PET scan, would potentially establish the role of the fibrillar amyloid in the primary prevention trials [68]. The key role of the fibrillar oligomers in AD disease is also confirmed by the biochemical data obtained from brain homogenates [69], where significant correlations were found between the levels of fibrillar oligomers and cognitive decline as well as the neuropathological hallmarks of AD [70]. It has been previously reported that 89% of the brain vessels from the apoE4 transgenic mice that showed evidence of hemorrhage contained fibrillar amyloid deposits, based on Thioflavine-S staining and confirmed by electron microscopy [71].…”
Section: Structural Changes On the Cortical Capillariesmentioning
confidence: 81%
“…We prepared soluble and insoluble (guanidine‐extractable) fractions of the homogenates for Aβ measurement as reported in previous studies 1, 5, 32, 55, 56, 57, 58.…”
Section: Methodsmentioning
confidence: 99%